2018
DOI: 10.3389/fpsyg.2018.02334
|View full text |Cite
|
Sign up to set email alerts
|

Reciprocal Effects Among Parental Homework Support, Effort, and Achievement? An Empirical Investigation

Abstract: The present study investigates reciprocal influences of parental homework support, effort, and math achievement, using two waves of data from 336 9th-graders. Results revealed that higher prior autonomy-oriented support and homework effort resulted in higher subsequent achievement. Higher prior content-oriented support led to higher subsequent effort, but lower subsequent achievement. Additionally, higher prior effort led to higher subsequent autonomy-oriented support. Furthermore, our results supported the st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
36
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 56 publications
0
36
0
1
Order By: Relevance
“…Parent involvement may also be different for boys and girls (Daniel et al, 2016;Dumont et al, 2012;Freund et al, 2018;Muntoni & Retelsdorf, 2019;Yurk, 2015). Research concerning the moderating effect of gender in parental involvement in homework has been inconsistent (Dumont et al, 2012;Luo et al, 2016;Silinskas & Kikas, 2019;Tárraga et al, 2017;Xu et al, 2018). Furthermore, studies have shown mixed findings concerning gender differences regarding the relationship between parental involvement in homework and student achievement (Rogers et al, 2009;Silinskas & Kikas, 2019).…”
Section: Moderating Role Of Gendermentioning
confidence: 99%
See 1 more Smart Citation
“…Parent involvement may also be different for boys and girls (Daniel et al, 2016;Dumont et al, 2012;Freund et al, 2018;Muntoni & Retelsdorf, 2019;Yurk, 2015). Research concerning the moderating effect of gender in parental involvement in homework has been inconsistent (Dumont et al, 2012;Luo et al, 2016;Silinskas & Kikas, 2019;Tárraga et al, 2017;Xu et al, 2018). Furthermore, studies have shown mixed findings concerning gender differences regarding the relationship between parental involvement in homework and student achievement (Rogers et al, 2009;Silinskas & Kikas, 2019).…”
Section: Moderating Role Of Gendermentioning
confidence: 99%
“…Despite its relevance, parental involvement in children's homework remains as a controversial topic among scholars who have not met a consensus on its effects on academic achievement (Dumont et al, 2012;Hill & Tyson, 2009;Moroni et al 2015). While some scholars (Fernández-Alonso et al, 2016;Xu et al, 2018) report parental involvement in homework as a consistent variable leading students to academic success, others have reported either a weak or a negative association (Barger et al, 2019;Hill & Tyson, 2009;Silinskas et al, 2013;Valle et al, 2015).…”
mentioning
confidence: 99%
“…A meta-analysis study found that parental homework involvement was significantly associated with students’ general achievement and mathematics achievement, though the effect sizes were very small (ES = 0.024; ES = 0.063) (Castro et al, 2015). However, parents’ content support, one form of parental support, is not always positively, even negatively, related to students’ academic performance (including mathematics performance); parents’ controlling or intrusive support impairs adolescents’ motivation and academic achievement (Levpuscek and Zupancic, 2009; Boonk et al, 2018; Xu et al, 2018). Specifically, research in parental involvement in homework, however, has found that parental involvement in homework both promoted and impaired students’ performance (Desimone, 1999; Cooper et al, 2000; Corno and Xu, 2004; Pomerantz et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, research in parental involvement in homework, however, has found that parental involvement in homework both promoted and impaired students’ performance (Desimone, 1999; Cooper et al, 2000; Corno and Xu, 2004; Pomerantz et al, 2005). Some researchers hold that the quality rather than the quantity of parental involvement in homework is crucial to students’ achievement (Trautwein et al, 2006; Knollmann and Wild, 2007), and revealed some dimensions that positively associate with academic engagement and achievement, for example, parental autonomy support (Cooper et al, 2000; Pomerantz et al, 2007; Katz et al, 2011; Dumont et al, 2012; Moroni et al, 2015; Boonk et al, 2018; Xu et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation